BioH2 from Dark Fermentation of OFMSW: Effect of the Hydraulic Retention Time and Organic Loading Rate - Inês Martins; Elena Surra; Márcia Ventura; Nuno Lapa (Applied Sciences, 2022)
Food wastes represent one third of all food produced worldwide. It is crucial to both prevent the production of food waste and recover the wasted fraction with the aim to valorizing it. In this context, the conversion of the organic fraction of municipal solid wastes (OFMSW) into bioH2 by dark fermentation (DF) is an important technology to valorize these wastes into renewable fuel. Nevertheless, the DF of OFMSW needs to be optimized for critical operational parameters. The main purposes of this study were to investigate (i) the effect of HRT during continuous bioH2 production through DF and (ii) the effect of organic loading rate (OLR) ruled by HRT. In this work, three HRTs (4, 5, and 6 d) were tested in a mesophilic continuous stirred-tank reactor (CSTR). The HRTs of 4, 5, and 6 days, corresponding to OLRs of 23.6, 18.0, and 10.6 g volatile solids (VS)·L−1·d−1, respectively, showed bioH2 yields of 8.48, 18.2, and 1.64 L·kg−1 VSinfluent with an H2 content of approximately 25, 32, and 5% v/v, respectively. An accumulation of volatile fatty acids (VFAs) was registered with the decrease in HRT, causing a decrease in bioH2 production. The 5 d HRT was the most favorable condition.